Teori Belajar Kognitif Dan Implementasi Dalam Proses Pembelajaran - Yossita Wisman (FKIP Universitas Palangka Raya, 2020)
Education is a conscious effort carried out by guiding, teaching and training students that can cause changes in students with the aim of achieving conformity between students and their environment. The theory underlying education is basically divided into inductive-oriented theory of association meaning that your building is in the development of education is based on units of knowledge, attitudes and skills to become more universal units, the flow in this theory is the flow of behaviorism or better known as the flow of stimulus-response. the flow that assumes that education is directed at the creation of new behaviors in students . Learning is an important part that cannot be separated from the education process. Learning is a process of changing behavior and mindset experienced by individuals. Cognitive learning theory emphasizes that the most important thing in the education process is how the process occurs rather than the results achieved.